The dynamics of disability : measuring and monitoring disability for social security programs - Wunderlich, Gooloo S.; Rice, Dorothy P.; Amado, Nicole L. (National Academy Press, 2002)
This report, originally developed for the Social Security Administration (SSA), analyzes the SSA's disability program, looks at recent and emerging disability trends, summarizes previous experience in researching disability, and makes recommendations on increasing the SSA's ability to meet policy demands in the 21st century. Information will be of interest to policy makers, researchers, disability officials, and medical and rehabilitation professionals. Annotation (c)2003 Book News, Inc., Portland, OR (booknews.com).